Evaluating Adoption Rate of Climate Smart Agriculture and Its Effectiveness on Income Levels Among Smallholder Farmers: A Case Study in Zone II of Bidibidi Settlement, Yumbe District - Hilary Santo Abugo (Uganda Christian University, 2025)
Climate change is a threat to agriculture productivity and the environment. Climate smart Agriculture (CSA) is an appropriate adaptation approach to climate change. It allows farmers to improve their production and livelihood despite the conditions of climate change. This study was set up to evaluate the adoption rate of CSA and its effectiveness on income levels among smallholder farmers: a case study in zone II of Bidibidi settlement, Yumbe district. Following threat to environment by nationals and also the agricultural activities by refugees in search of settlement, the local government and NGOs have promoted CSA in recent years to solve these challenges and climate change. However, the effects of these practices on income levels of smallholder farmers have not been studied and documented. This study targeted 68 farmers who are beneficiaries CSA training by an NGO. Data was collected on CSA practices commonly practiced, demographic and socioeconomic characteristics of farmers to determine factors influencing adoption of CSA practices as well as data on income from crop sales from previous season. Data was analysed using SPSS. Descriptive statistics was used for CSA practices adopted by farmers, factors influencing adoption of CSA practices were analysed using binary logistic regression and Pearson 2tailed correlation, multilinear regression were used to analyse the relationship between adoption of CSA and income. The study results indicated that 100% of famers adopted row planting, 97.1% early planting and 88.2% use drought resistant crop, membership in farmers’ group significantly boost the likelihood of intercropping, mulching, block farming, early planting, crop rotation and drought resistant crop varieties while firm size and employment influence adoption of agroforestry and access to extension negatively influence the adoption of some CSA practice. The study result found out that there is a positive moderate correlation between adoption of CSA practices and income from crop sales (Pearson’s r= 0.0368) significant(p=0.002) meaning CSA practices increases income of farmers. There is need of more efforts to enhance adoption of less adopted CSA practices such irrigation, agroforestry and conservation tillage.
Undergraduate